Toxicities and costs of placing prophylactic and reactive percutaneous gastrostomy tubes in patients with locally advanced head and neck cancers treated with chemoradiotherapy. Issue 8 (27th November 2013) - Baschnagel, Andrew M.; Yadav, Siddhartha; Marina, Ovidiu; Parzuchowski, Aaron; Lanni, Thomas B.; Warner, Jillian N.; Parzuchowski, Jeanne S.; Ignatius, Renjitha T.; Akervall, Jan; Chen, Peter Y.; Krauss, Daniel J.
ABSTRACT Background We compared dependence rates, complications, toxicities, and costs associated with prophylactic versus reactive percutaneous endoscopic gastrostomy (PEG) tube placement. Methods One hundred ninety‐three patients with locally advanced head and neck squamous cell carcinoma treated with concurrent chemoradiotherapy were retrospectively reviewed. Results The 1‐year and 2‐year actuarial PEG tube dependence rate of the entire cohort was 24% and 13%, respectively. There was no difference in the PEG tube dependence rates between those placed prophylactically versus reactively. Patients who received a PEG tube reactively had a significantly higher stricture rate (p = .03) and aspiration rate (p < .001) compared to the prophylactic group. There were significantly fewer hospitalizations in the prophylactic group compared to the reactive group (p = .003). When accounting for both PEG placement and hospitalizations, the prophylactic approach was found to be more cost effective. Conclusion PEG tubes placed prophylactically were associated with lower rates of strictures, aspirations, hospitalizations, and costs compared to those placed reactively. © 2013 Wiley Periodicals, Inc. Head Neck 36: 1155–1161, 2014